2015
DOI: 10.1002/pssc.201510127
|View full text |Cite
|
Sign up to set email alerts
|

Comparative contributions of singlet and triplet excitons in the performance of organic devices

Abstract: The properties of singlet and triplet excitons are compared in organic materials for applications in optoelectronic organic solar cells (OSCs) and organic light emitting devices (OLEDs). It is found that by managing the organic material designs both singlet and triplet excitons can be beneficially used in OSCs and OLEDs equally well. A model of dissociation of excitons excited in the acceptor material of the bulk heterojunction organic solar cells is presented. It is shown that the dissociation of acceptor exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Therefore, this FRET process is likely to initiate the two-step exciton dissociation process, which first includes large-scale FRET exciton diffusion from D to DA, and then dissociation at the DA/A interface. However, the FRET process, to be efficient, needs overlapping between the D emission spectrum and the DA absorption spectrum [35][36][37]. In the present case, the absorption spectrum of AlPcCl exhibits two main features, one band between 550 nm and 800 nm and the other one in the UV range from 400 nm and less (Figure 4).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Therefore, this FRET process is likely to initiate the two-step exciton dissociation process, which first includes large-scale FRET exciton diffusion from D to DA, and then dissociation at the DA/A interface. However, the FRET process, to be efficient, needs overlapping between the D emission spectrum and the DA absorption spectrum [35][36][37]. In the present case, the absorption spectrum of AlPcCl exhibits two main features, one band between 550 nm and 800 nm and the other one in the UV range from 400 nm and less (Figure 4).…”
Section: Resultsmentioning
confidence: 68%
“…Indeed, we had already shown that AlPcCl can be used as an acceptor layer in binary OPVs [28]. Depending on the organic materials chosen to build the active layer, different models can be used to describe the operating mechanism of ternary OPVs, which are as follows: (i) the classical charge transfer via the four-step process, (ii) the parallel mechanism of which the ternary structure behaves as if it was two diodes in parallel [42], (iii) the formation of an interpenetrating bulk heterojunction structure, which is possible when there is a high degree of compatibility between the donor and the acceptor materials [43], and, finally, (iv) the energy transfer mechanism by Föster resonance energy transfer (FRET) [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…This is physically reasonable, since triplet polaron pairs can be expected to be more strongly bound than singlets. This is certainly true of triplet versus singlet excitons 35 and a more strongly bound pair is expected to have a smaller probability of dissociation. The microscopic parameters obtained by fitting the sample results in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the fact that as the two materials, donor and acceptor, are blended together in a BHJ structure, they cannot be separately excited experimentally. However, in order to understand the contributions This has prompted several researchers to investigate the above two processes in more detail [37][38][39][40][41][42][43][44][45][46]. Recently, two different external quantum efficiencies (EQE) due to different donor and acceptor absorption bands have been reported [37].…”
Section: Introductionmentioning
confidence: 99%
“…These energy offsets are independent of the pathway of the formation of CT excitons. Singh et al [45,46] recently studied the contribution of exciton generation in the donor and acceptor materials and its dissociation to the performance of BHJ OSCs. They found that the absorption and dissociation rates as well as exciton diffusion lengths are comparable whether excitons are generated in the donor or acceptor.…”
Section: Introductionmentioning
confidence: 99%